Are people having adequate knowledge to prevent COVID-19 pandemic? A cross-sectional study - Kaur, Rashpinder; Sharma, Poonam; ., Deepika; Kaur, Pavit; ., Rajni; Gill, Suchpreet Kaur (International Journal Of Community Medicine And Public Health, 2021)
Background: The Covid-19 pandemic is still going on around the globe and prevention of this pandemic is depend on how much people are aware regarding COVID-19 disease. The present study was conducted with an aim to determine the level of knowledge towards COVID-19 among people. Methods: Present study included cross sectional descriptive survey design which was conducted on 366 participants who visited in university during 2020. Convenient sampling technique was chosen for selection of samples. A self-structured knowledge questionnaire was used for data collection. Descriptive and inferential statistics were used to analyse the data in SPSS. Results: Study findings revealed that there were 343 (93.7%) female participants and were students (86.3%). Overall, more than half (60.1%) of participants had good knowledge while 37.2% had average knowledge on COVID-19. Significant difference was found among participants’ group (p>0.001), gender (p=0.021), education (p=0.002), marital status (p=0.002), age (p=0.021), and inhabitants (p=0.002 Participants showed poor knowledge on COVID-19 susceptibility (81%) and diagnosis (90%) aspects. Conclusions: Study concluded that many people were still had average and poor knowledge on COVID-19. Higher authorities must find the ways for making people more aware on this pandemic to control its impact.